2011
DOI: 10.5539/jas.v3n1p194
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Determinants of Land-use Intensity among Food Crop Farmers in Southwestern Nigeria

Abstract: Increased food production in Nigeria has over the years been attributed to area expansion while reports of shortened fallow period of farmlands are suggestive of shift towards intensification. The study examines the structure of land-use intensification in food crop production in Southwestern Nigeria towards determining its drivers and concordance with condition for sustainable intensification. The results showed that land-use intensification is characterized by high frequency of cultivation (79%) and high cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, the size of farm land owned and fertility status would influence farmers' ultimate farm investment decisions and weather information seeking behaviour due to the enormity of expected losses in the event of unexpected weather [19]. Saka et al [55] and Lawal et al [56] emphasized that soil fertility status would influence the pattern of crop combination although degraded plots of land are often left to fallow and regain fertility for future uses.…”
Section: Probit Regression Results Of Factors Influencing Access To Wmentioning
confidence: 99%
“…In addition, the size of farm land owned and fertility status would influence farmers' ultimate farm investment decisions and weather information seeking behaviour due to the enormity of expected losses in the event of unexpected weather [19]. Saka et al [55] and Lawal et al [56] emphasized that soil fertility status would influence the pattern of crop combination although degraded plots of land are often left to fallow and regain fertility for future uses.…”
Section: Probit Regression Results Of Factors Influencing Access To Wmentioning
confidence: 99%
“…In other words, land-use intensification is a process of continuous or permanent cultivation/farming on a fixed land area with an increased rate of utilization of other farm inputs such as labour, fertilizers, manure, as well as improved seeds in order to obtain optimum farm produce [8][9][10][11] . Past studies have reported that agricultural intensification depends on efficient land use and proper reallocation of farm resources [12][13][14] . In addition, it is noticeable that some of the efforts made by farmers and governments to increase farm production efficiency have not effectively achieved the major goal of self-sufficiency in food production in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In West African savannahs, rural population growth is contributing to an expansion of areas under cultivation and larger livestock herds, resulting in increasing conflicts between crop farmers and livestock farmers over agro-pastoral resources. This demographic pressure also is the principal reason behind shortened fallow periods, with consequent reductions in soil fertility and in the productivity of farming systems (Dugué & Dongmo Ngoutsop, 2004;Saka, Okoruwa, Oni, & Oyekale, 2011). For several decades, development research has proposed technical options based on a better integration of agriculture and livestock production to help farmers increase their agriculture production levels while protecting their agro-pastoral resources (Sumberg, 1998).…”
Section: Introductionmentioning
confidence: 99%